POPULASI RAYAP PADA PERTANAMAN LADA DI WAY KANAN, LAMPUNG - Agus M. Hariri, F.X. Susilo, dan Hamim Sudarsono . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2003)
Termite population on black pepper plantation in Way Kanan, Lampung. This survey conducted from July to August 2002 was aimed to document the abundance and the diversity of termites at two locations of black pepper plantation with different soil covers at Way Kanan District, Lampung. The first location (Tiuhbalak) was practically bare (less weeds and more litter) while the second location (Sukarame) was more covered (more weeds and less litter). Two termite transects were set at each location. Each transect, comprised of 20 sections of 5 m x 2 m, was laid down in an oblique direction relative to the black pepper plant row. Termites were collected by soil scrapping, wood dismantling, and/or circum-digging of the soil around the plants by two collectors in 30 minutes/section. Termite specimens (mainly soldier caste) were conserved into vial containing 70% of ethanol for identification. Variables being observed included termite’s (1) relative abundance, (2) distribution, (3) number, and (4) biomass. The relative abundance and distribution between locations were compared using F-test at 5% level of significance. Results showed that the termites recovered from 7.5 finds (Tiuhbalak) and 10 finds (Sukarame) were Macrotermes gilvus, Microtermes obesi, Nasutitermes havilandi, Havilanditermes sp., Schedorhinotermes medioobscurus, and Cryptotermes sp.. Termites that were found in association with the black pepper plants were M. gilvus (in part) and Cryptotermes sp., while the other M. gilvus, M. obesi, N. havilandi, Havilanditermes sp., and S. medioobscurus were found from their sub-terranean nests close to the plants. Higher termite number and biomass (dominated by M. gilvus) were recovered from Tiuhbalak, while higher termite diversity was observed from Sukarame.